Retention Limitations and Impacts of Wisdom Inheritance on Social and Cultural Jointly Identities on ASEAN Region : Thailand, Laos and Cambodia - Jantanukul, Dr.Watcharaporn (Journal for Developing the Social and Community, 2018)
This article was part of the research title “Establish the Collaborative System to Preserve and Protect the Wisdom of Society and Culture Inheritance on ASEAN Region : Thailand, Laos and Cambodia”. There were aim to study the retention limitations and impacts of wisdom inheritance on social and cultural jointly identities. The data sources were; 1) relevant documents and evidence, concepts, theories and related research and 2) target population comprising Buddhist monks, academics, experts, and other agencies concerned from three countries, they were 21 persons that selected by snow-ball sampling. The research results were found that; (1) the retention limitations of society and culture inheritance on ASEAN region were; changes in the economy, Political regime, value awareness of wisdom heritage, labor mobility, and external changes in the country. In addition, (2) the impacts of retention found that; impact of living, environment, social system and agriculture and agricultural products.